The fight against corruption is the main task of society - Umarov Zokir Raupovich (Genius Journals, 2023)
The article discusses issues such as laws adopted in the field of anti-corruption measures in the country and the norms established in it, as well as measures carrying out the state in order to prevent corruption
Keywords: corruption; fight against corruption; concept of corruption